Transformasi Instrumen Internasional dalam Pelindungan Pekerja Migran Perempuan dan Implikasinya terhadap Kebijakan Nasional - M. Mustofah Bisri; Safira Ika Maharani; Barlian Najma Elhanuna (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study analyzes the transformation of international instruments in the protection of female migrant workers and their implications for Indonesia’s national policy from an Administrative Law perspective. It focuses on CEDAW 1979, ICMW 1990, and ILO Conventions No. 189 and No. 190. Using a normative legal approach with secondary data from legislation, government reports, and academic sources, the study finds that despite ratification of CEDAW and ICMW, non-ratification of ILO No. 189 and incomplete implementation of Law No. 18 of 2017 result in gaps in legal protection, particularly for domestic and informal female migrant workers. Challenges include weak oversight of placement agencies, irregular migration, gender-based violence, and limited enforcement of labor rights. The findings suggest that international instruments provide a strong normative framework, yet practical protection remains limited. The study recommends ratifying ILO Conventions No. 189 and 190, harmonizing national policies with international standards, strengthening administrative oversight, and promoting empirical research to evaluate policy effectiveness in protecting female migrant workers.